Body composition characteristics vs a subjective assessment of body mass and eating habits by female wrestlers using the example of the Polish national youth team - Piepiora, P.; Superson, M.; Witkowski, K.; Maslinski, J.; Migasiewicz, J. (Archives of Budo Science of Martial Arts and Extreme Sports, 2018)
Background & Study Aim Controlling the body mass in long-term carteer of combat sports athletes is one of the most important health strategies. The aim of the study was the relationship between body weight and body fat level and correlation of body mass and composition with the subjective assessment of body weight and eating habits of the wrestlers.